Encyclopedia of Hydrological Sciences 2005
DOI: 10.1002/0470848944.hsa317
|View full text |Cite
|
Sign up to set email alerts
|

Contaminated Sediments: Inorganic Constituents

Abstract: Owing to a variety of physical and chemical factors, in conjunction with aquatic physicochemical conditions, fluvial/lacustrine suspended and bed sediments can act as both sources and carriers of a wide variety of inorganic constituents and nutrients. Many of these constituents reflect local environmental conditions and are derived from both point and nonpoint sources. When sources have an anthropogenic origin, and chemical levels exceed the typical range of local baseline concentrations, sediments can be desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…Turbidity, which results from variations in SSC and color, is responsible for most current sediment-associated total maximum daily load (TMDLs) calculations. , Other than SSCs and/or turbidity, sediment-associated chemical concentrations largely are unregulated because there are few if any established limits for sediment-associated chemical constituents. The reasons for this appear to relate to disagreements over how to estimate sediment-associated constituent bioavailability. Currently, only five countries regulate sediment-associated chemical constituents: Canada, New Zealand, Australia, The Netherlands, and Germany; however, many have established guidelines. , Contrariwise, when environmental/water-quality monitoring program objectives are nonregulatory, for example, estimating annual fluxes for various chemical constituents (Figure ; SI Figure 3), or the determination/identification of the sources/sinks of suspended sediment (e.g., sediment fingerprinting), or identifying water-quality trends, or for evaluating land-use impacts, or in dealing with eutrophication issues, then sediment-associated chemical constituents should be included. ,, …”
Section: Sample Mediamentioning
confidence: 99%
See 2 more Smart Citations
“…Turbidity, which results from variations in SSC and color, is responsible for most current sediment-associated total maximum daily load (TMDLs) calculations. , Other than SSCs and/or turbidity, sediment-associated chemical concentrations largely are unregulated because there are few if any established limits for sediment-associated chemical constituents. The reasons for this appear to relate to disagreements over how to estimate sediment-associated constituent bioavailability. Currently, only five countries regulate sediment-associated chemical constituents: Canada, New Zealand, Australia, The Netherlands, and Germany; however, many have established guidelines. , Contrariwise, when environmental/water-quality monitoring program objectives are nonregulatory, for example, estimating annual fluxes for various chemical constituents (Figure ; SI Figure 3), or the determination/identification of the sources/sinks of suspended sediment (e.g., sediment fingerprinting), or identifying water-quality trends, or for evaluating land-use impacts, or in dealing with eutrophication issues, then sediment-associated chemical constituents should be included. ,, …”
Section: Sample Mediamentioning
confidence: 99%
“…Inorganic constituents that primarily are sediment-associated are called hydrophobes, and normally are bound to sediment particle surfaces . This group includes heavy metals/trace elements (e.g., Pb, Zn, Hg) and nutrients (e.g., N, P).…”
Section: Sample Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Particle size fractionation has been used to investigate land use and fluvial deposition of contaminated mine waste (Horowitz & Stephens, 2008;Horowitz, 1993Horowitz, , 1988Horowitz, , 2008. Horowitz (2008) and others used air elutriation to evaluate each fraction of contaminated sediment and found that the finer aeolian fraction contained 10 times more metals than the larger fractions (Callender, 1988;Lu et al, 2012).…”
Section: Wind Transport Of Contaminantsmentioning
confidence: 99%
“…Horowitz (2008) and others used air elutriation to evaluate each fraction of contaminated sediment and found that the finer aeolian fraction contained 10 times more metals than the larger fractions (Callender, 1988;Lu et al, 2012). When using this method of evaluating the lighter fractions, it was obvious that contaminants associated with the smaller particles can be transported farther (compared to shorter transport for larger size particulates) and deposited by aeolian processes in areas where there is no anthropogenic activities (Horowitz & Stephens, 2008;Lu et al, 2012).…”
Section: Wind Transport Of Contaminantsmentioning
confidence: 99%